2020
DOI: 10.1007/s11892-020-01347-3
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Sodium-Glucose Co-Transporter-2 Inhibitors Stand out in Heart Failure?

Abstract: Purpose of Review We highlight the unique properties of the sodium-glucose cotransporter-2 (SGLT-2 inhibitors) which may lend favorably to their efficient integration in the background of other heart failure (HF) therapies. We also discuss the unique aspects of SGLT-2 inhibitor dosing, lack of titration needs, effects on kidney function and electrolytes, diuretic activity, and safety in the high-risk peri-hospitalization window. Recent Findings Dapagliflozin was recently approved for the treatment of heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Angiotensin receptor neprilysin inhibitor (ARNI), beyond blocking angiotensin II signaling, augments natriuretic peptides by inhibiting their breakdown by neprilysin, and becomes class I drug recommended for the treatment of heart failure in the recent years [6]. At present, more attention was paid to the effects of SGLT2i on cardiovascular system [7][8]. A recent nationwide population-based longitudinal cohort study revealed that patients with type 2 diabetes prescribed with SGLT2i were associated with a lower risk of all-cause mortality and new-onset arrhythmias compared with those not taking SGLT2i in real-world practice [9].…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin receptor neprilysin inhibitor (ARNI), beyond blocking angiotensin II signaling, augments natriuretic peptides by inhibiting their breakdown by neprilysin, and becomes class I drug recommended for the treatment of heart failure in the recent years [6]. At present, more attention was paid to the effects of SGLT2i on cardiovascular system [7][8]. A recent nationwide population-based longitudinal cohort study revealed that patients with type 2 diabetes prescribed with SGLT2i were associated with a lower risk of all-cause mortality and new-onset arrhythmias compared with those not taking SGLT2i in real-world practice [9].…”
Section: Introductionmentioning
confidence: 99%
“…As the global number of patients with type 2 diabetes mellitus (DM2) approaches 500 million, that of patients with heart failure (HF) reaches 64 million. [1][2][3] HF and DM2 often co-occur, resulting in a worse prognosis for both conditions. Records suggest that DM2 can be present in up to 40% of patients with HF and reduced ejection fraction (EF) and up to 45% of those with preserved EF.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 More recently, the beneficial effects of SGLT2 inhibitors on the reduction of cardiovascular events in adequately treated patients with symptomatic HF (New York Heart Association [NYHA] functional class >/= II) with reduced EF (< 40%) led the United States Food and Drug Administration (FDA) and the Brazilian Health Regulatory Agency (Agência Nacional de Vigilância Sanitária; Anvisa) to extend the indication of SGLT2 inhibitors to the treatment of symptomatic HF with reduced EF. 1,4,6 SGLT2 receptors are present in the proximal convoluted tubules of the kidney and mediate glucose uptake, accounting for 90% of renal glucose reabsorption. The inhibition of SGLT2 receptors leads to a reduction in their ability to reabsorb glucose, promoting its excretion in urine and leading to a reduction in plasma glucose levels.…”
Section: Introductionmentioning
confidence: 99%